Spanish interference in EFL writing skills: A case of Ecuadorian senior high schools - Cabrera Solano, P. (2014)
Extensive studies have been conducted regarding mother tongue (L1) interference and developing English writing skills. This study, however, aims to investigate the influence of the Spanish language on second language (L2) writing skills at several Ecuadorian senior high schools in Loja. To achieve this, 351 students and 42 teachers from second year senior high schools (public and private) were asked to participate in this study. The instruments for data collection were student and teacher questionnaires, as well as a written test in which students were asked to write a narrative passage. The information gathered from the instruments was then organized and tabulated to determine the various interference variables. Afterwards, the most representative samples from the narrative texts were analyzed based on their semantic, morphological and syntactical features. The results from this study indicate that English grammar and vocabulary were the linguistic areas that suffered the highest level of L1 language interference. The most common Spanish interference errors were misuse of verbs, omission of personal and object pronouns, misuse of prepositions, overuse of articles, and inappropriate/ unnatural word order. Finally, some suggestions are given to teachers in order to help students prevent further Spanish interference problems during writing/composition classes.